Origins of the Sicilian mafia: The market for lemons - Arcangelo Dimico; Alessia Isopi; Ola Olsson (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2012)
Since its first appearance in the late 1800s, the origins of the Sicilian mafia have remained a largely unresolved mystery. Both institutional and historical explanations have been proposed in the literature through the years. In this paper, we develop an argument for a market structure-hypothesis, contending that mafia arose in towns where firms made unusually high profits due to imperfect competition. We identify the market for citrus fruits as a sector with very high international demand as well as substantial fixed costs that acted as a barrier to entry in many places and secured high profits in others. We argue that the mafia arose out of the need to protect citrus production from predation by thieves. Using the original data from a parliamentary inquiry in 1881-86 on all towns in Sicily, we show that mafia presence is strongly related to the production of orange and lemon. This result contrasts recent work that emphasizes the importance of land reforms and a broadening of property rights as the main reason for the emergence of mafia protection.
Keywords: 330; mafia; Sicily; protection; barrier to entry; dominant position